2016
DOI: 10.4041/kjod.2016.46.2.111
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors associated with the success rates of posterior orthodontic miniscrew implants: A subgroup meta-analysis

Abstract: ObjectiveTo systematically review previous studies and to assess, via a subgroup meta-analysis, the combined odds ratio (OR) of prognostic factors affecting the success of miniscrew implants (MIs) inserted into the buccal posterior region.MethodsThree electronic searches that were limited to articles on clinical human studies using MIs that were published in English prior to March 2015 were conducted. The outcome measure was the success of MIs. Patient factors included age, sex, and jaw of insertion (maxilla v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 34 publications
3
36
0
3
Order By: Relevance
“…This finding was not in accordance with other studies, which found that there was no significant differences between adolescents and adults. However, two systematic reviews and meta‐analyses conducted in this context concluded that higher age group has higher success rate than lower age group . It is logical that the reason behind the higher success rate in the higher age group is related to higher bone density found in adults, and bone quality is a major factor in the success of TAD …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was not in accordance with other studies, which found that there was no significant differences between adolescents and adults. However, two systematic reviews and meta‐analyses conducted in this context concluded that higher age group has higher success rate than lower age group . It is logical that the reason behind the higher success rate in the higher age group is related to higher bone density found in adults, and bone quality is a major factor in the success of TAD …”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic reviews and meta‐analysis concluded that the factors determining success rates were inconsistent between the studies . Another review confirmed a correlation between failure rate and specific factors, while another limited the success or failure to the TAD placement area; higher success in the posterior buccal bone is always observed . This confirms that studies focusing on the effect of all‐collective factors are still scarce, and further investigations are warranted.…”
Section: Introductionmentioning
confidence: 87%
“…, 4 , 8 , 14 , 15 , 16 , 17 Although mini-implants with a reduced diameter have increased risk of fracture, the choice of mini-implants with a diameter that is too large can lead to bone necrosis through micro fractures in bone, and dental structures risks 15 16 …”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the difference in surface roughness; the ideal value for osseointegration has been suggested to be between 1.0–1.5 µm 222930. The surface roughness31 of the hybrid group was assumed to produce a higher osseointegration32 capacity than that of the etched group.…”
Section: Discussionmentioning
confidence: 99%